The effectiveness of activated charcoal in feed on histopathological features of the spleen of tilapia (Oreochromis niloticus) exposed to organophosphate insecticides - Nurhayati, Nurhayati; Auzan, Shahibul; Handayani, Lia; Thaib, Azwar; Haja Almuqaramah, T M; Syahputra, Faisal (Universitas Malikussaleh, 2023)
Excessive and periodic use of insecticides has a negative impact on aquatic areas and the biota in them. Pesticides that accumulate in the aquatic environment affect the life non target organisms such as fish. In addition, pesticides can cause damage to the gills, liver, intestines and spleen. This organ plays an important role in the immune system. Thus, an alternative is needed to overcome this problem, one of which is the addition of activated charcoal in the feed. The aims of study to determine the effect of the use of activated charcoal in feed on the histopathological description of the spleen of tilapia exposed to organophosphate pesticides. The study was conducted experimentally by applying 4 treatments and 2 replications as the treatments used included T1 (0% activated charcoal); T2 (1% activated charcoal); T3 (2% activated charcoal); T4 (3% activated charcoal). The test fish used were tilapia measuring 7 ± 0,4 cm long with a stocking density of 30 fish/container. Parameters observed were histopathological description of tilapia spleen at pre exposure, post exposure and after administration of activated charcoal. The results of observations of tissue damage were analyzed descriptively qualitatively and presented in the form of images. The results showed that the addition of 2% activated charcoal (T3) in the feed was able to reduce damage to the spleen due to exposure to organophosphate insecticides. Keywords: Activated charcoal; feed; insecticide; spleen